Technological innovations in aquaculture with special reference to intelligent aquaculture - Parakkandi, Jesna; Ramya, Vijayakumar Leela; Panikkar, Preetha; Das, Basanta Kumar (Indian Farming, 2024)
Technological interventions in aquaculture have led to many fold increase in the aquaculture production of finfish and shellfish in several countries across the world. These technologies cover the fields of fish genetics, nutrition, health management, aquaculture system designs as well as the harvesting and marketing of the produce. However, a new intervention includes the application of artificial intelligence in aquaculture. This includes the collection of data on fish and the environment, transmitting it to the control centre followed by the data processing and decision making stages using cloud platform and internet of things. This technological innovation has paved the way forward for the development of an automated aquaculture system, thereby transforming this industry to the next level of production and sustainability.